Virtual Reality as a Remote Workspace Platform: Opportunities and Challenges - Fereydooni, Nadia; Walker, Bruce N. (2020)
ABSTRACT Millions of people all around the world are participating in an unprecedented experiment of working from home due the Covid-19 pandemic. There is no doubt that Working from Home (WFH) brings many benefits to the workers, including flexibility of hours and less commute. The problems associated with this working style include distractions, and lack of appropriate space and work-life separation. Through surveying the literature in this paper, we show that virtual reality (VR) has the capability to amplify benefits associated with WFH and assist workers in tackling its challenges. We then discuss some of the challenges that need to be considered and tackled to effectively work in virtual environments at home. Keywords working from home, virtual reality, head-mounted displays, notifications, interruption ABOUT THE AUTHOR/S Nadia Fereydooni Georgia Institute of Technology Atlanta, USA nadia.fereydooni@gatech.edu Nadia Fereydooni is a Human-Centered Computing doctoral student at Georgia Institute of Technology. She earned her Bachelors degree in Computer Engineering from University of New Hampshire. Her research focuses on the use of Virtual Reality in automated vehicles to provide rich, immersive experiences while maintaining passengers' trust and safety.. https://nadiafereydooni.weebly.com/ Bruce N. Walker Georgia Institute of Technology Atlanta, USA bruce.walker@psych.gatech.edu Bruce N. Walker is a Professor at Georgia Tech, in the Schools of Psychology and Interactive Computing. His Sonification Lab studies the human-computer interaction (HCI) issues in non-traditional interfaces, ranging from mobile devices, to cockpits and vehicle displays, to multimodal interfaces in education and in complex task environments. Particular research interests include sonification and auditory displays. New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).